Penerapan Metode Moora dalam Penilaian Kinerja Guru di SMK Negeri 3 Kota Bengkulu - Vivi Yesinthia; Siswanto Siswanto; Indra Kanedi (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Every school must have a Teacher Performance Assessment (PKG), one of which is SMK Negeri 3 Bengkulu. At this school, teacher performance assessments are carried out annually based on predetermined criteria. However, in the assessment process it is still done manually, the impacts that occur are errors in giving grades and differences in understanding between teachers because they feel less satisfied and inaccurate grades, causing instability in the teaching and learning process as well as gaps between teachers in schools. The teacher performance assessment application at SMK Negeri 3 Bengkulu City is an application that is used to facilitate the process of managing teacher performance assessment data in schools, where this application is made using the Visual Basic .Net programming language and SQL Server 2008r2 database. In this application, one of the Decision Support System Methods (DSS) has been applied, namely the Moora Method, so that the final result of the evaluation of teacher performance assessment is based on the calculation of the Moora Method. This can be used as an alternative in helping the school to add additional benchmarks for evaluating teacher performance assessment through the Moora Method approach which is calculated computerized so that the final score for each teacher will be made a ranking of the highest value to the lowest value. Based on the results of black box testing, the functionality of the teacher performance appraisal application at SMK Negeri 3 Bengkulu City has been running as it should and is able to display the final results of the teacher performance assessment based on the Moora Method process.